2006
DOI: 10.1007/s11243-005-6400-5
|View full text |Cite
|
Sign up to set email alerts
|

Metallosurfactants of Chromium(III) Coordination Complexes. Synthesis, Characterization and Determination of CMC Values

Abstract: A number of mixed ligand chromium(III)-surfactant coordination complexes, of the type cis-[Cr(en) 2 (A)X] 2+ and cis-a-[Cr(trien)(A)X] 2+ (A = Dodecyl or Cetylamine; X = F ) , Cl ) , Br ) ) were synthesized from the corresponding dihalogeno complexes by ligand substitution. These compounds form foam in aqueous solution when shaken. The critical micelle concentration (CMC) values of these surfactant metal complexes in aqueous solution were obtained from conductance measurements. Specific conductivity data (at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…In these derivatives a small difference in the head group structure have a large effects on the CMC values and also CMC values decreased to approximately two times for every additional methylene residue in the hydrophobic group. As mentioned in our previous reports [44][45][46] , the CMC values (Table 2) for surfactant-S163 cobalt(III) complexes in the present study are also very low compared to that of the simple organic surfactants. Thus it is suggested that these metal surfactant complexes have more capacity to associate themselves forming aggregates compared to those of ordinary synthetic organic surfactants.…”
Section: In Aqueous Solutionsupporting
confidence: 61%
See 2 more Smart Citations
“…In these derivatives a small difference in the head group structure have a large effects on the CMC values and also CMC values decreased to approximately two times for every additional methylene residue in the hydrophobic group. As mentioned in our previous reports [44][45][46] , the CMC values (Table 2) for surfactant-S163 cobalt(III) complexes in the present study are also very low compared to that of the simple organic surfactants. Thus it is suggested that these metal surfactant complexes have more capacity to associate themselves forming aggregates compared to those of ordinary synthetic organic surfactants.…”
Section: In Aqueous Solutionsupporting
confidence: 61%
“…The surfactant-cobalt(III) complexes of the present study were prepared as given below using a method similar to the same type of complexes reported in the literature as well as in our previous work 8,30 .…”
Section: Synthesis Of Double Chain Surfactant-cobalt(iii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cationic surfactants are the most widely used class of surfactants in both industrial practice and academic research, being utilized in practical applications ranging from household uses, including detergents, pharmaceuticals, and personal care products, to industrial applications involving coatings and lubricants 2. In previous papers 3–6, we have reported the influence of temperature on the behavior of some novel Co(III) and Cr(III) metallosurfactants in aqueous and nonaqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Micelle‐forming properties and electron‐transfer reactions of many surfactant metal complexes of similar nature to ordinary systems have been studied in our laboratories for a long time . In all these surfactant–metal complexes, the coordination complex containing a central metal ion with surrounding ligands coordinated to metal acts as a surfactant.…”
Section: Introductionmentioning
confidence: 99%